Influence of Kenyan Youth’s Perception towards Agriculture and Necessary Interventions; a Review - Njeru, Lucy K.; Gichimu, Bernard M. (Science Domain, 2015)
Approximately 64% of unemployed persons in Kenya are youth, most of which live in rural areas and lacks formal education and vocational or professional skills. In spite of this, youth participation in agriculture has been relatively low in the country. This may be partly attributed to, among other factors, thepoor perception of the youth on agriculture. Agriculture which is basically a ruraloriented sector remains the backbone of the Kenya’s economy contributing over 30% of GDP. The sector provides over 80% of employment opportunities in the country but remains unattractive to the youth. This implies that most of the Kenyan youth are not fully engaged in productive economic activities which put their dependency index quite high. If the perception of youth towards agriculture is not changed, they will remain a big burden to the society and to their families in particular. There are various activities along the agriculture value chain which the youths can engage in to ensure their self-reliance and create employment thus reducing youth-related social problems and improving national economic growth and self-sufficiency. The paper seeks to analyze and discuss the influence of Kenyan youth’s perception towards agriculture and required interventions. This information will be useful in developing policies that will make agriculture attractive to the youth.
Keywords: Youth; agriculture; Employment; Economy; Kenya